2020
DOI: 10.1002/adom.202001034
|View full text |Cite
|
Sign up to set email alerts
|

Wafer‐Scale Fabrication of 2D β‐In2Se3 Photodetectors

Abstract: Nevertheless, the research of 2D materials is still in its early stages. The field started with graphene several years ago, [3] but more materials have been added continuously to the list. Among these, transition metal dichalcogenides (TMDC), [4] which have impressive optical properties in the visible range, are currently one of the most studied 2D materials. Devices made of these materials have shown remarkable performance as photodetectors, [5,6] nonvolatile random access memory, [7] or photovoltaics, [8] ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…It will trigger new research enthusiasm whenever a new type of layered material is found or synthesized, which is because of its strong light-matter interaction, intrinsic flexibility, as well as external tunability of device potential profile and performance by electrostatic doping, electrochemical regulation, and interface engineering, etc ( Kang et al., 2020 ; Li et al., 2017 ; Mennel et al., 2020 ). In recent years, with the development of micro-nano processing technology and material synthesis methods, the wafer-level preparation of 2D materials has developed vigorously, which makes it possible to develop large-scale integrated retinomorphic optoelectronic devices ( Claro et al., 2021 ; Hou et al., 2021 ; Tong et al., 2019 ).…”
Section: Advanced Machine Vision System With Retinomorphic Optoelectronic Devicesmentioning
confidence: 99%
“…It will trigger new research enthusiasm whenever a new type of layered material is found or synthesized, which is because of its strong light-matter interaction, intrinsic flexibility, as well as external tunability of device potential profile and performance by electrostatic doping, electrochemical regulation, and interface engineering, etc ( Kang et al., 2020 ; Li et al., 2017 ; Mennel et al., 2020 ). In recent years, with the development of micro-nano processing technology and material synthesis methods, the wafer-level preparation of 2D materials has developed vigorously, which makes it possible to develop large-scale integrated retinomorphic optoelectronic devices ( Claro et al., 2021 ; Hou et al., 2021 ; Tong et al., 2019 ).…”
Section: Advanced Machine Vision System With Retinomorphic Optoelectronic Devicesmentioning
confidence: 99%
“…[26,28] The properties of the as-grown CIS nanoflakes were also better or comparable with those of other as-grown 2D materials. [35,58,62,63] Particularly in the near-infrared region, the as-grown CIS nanoflakes exhibited the outstanding optoelectrical characteristics that they were much better than those of the other as-grown 2D materials. [59][60][61] Furthermore, compared to the mechanical exfoliated multi-layer InSe, [8] the as-grown CIS nanoflakes were much sensitive to the weak near-infrared signal with higher photoresponsivity and specific detectivity.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…On the other hand, recent growth advances show that high-quality and strainfree PTMCs are not yet available and pristine material information are still inaccessible due to the formation of Te oxide on the surface 22 . In particular, limited reports are available on MBE of InSe 23 and GaSe 24,25 , whereas GaTe materials are at an early stage of development [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%